Conceptualizing urban adaptation to climate change: Findings from an applied adaptation assessment framework - Katie Johnson; Margaretha Breil (Fondazione Eni Enrico Mattei (FEEM), 2012)
Urban areas have particular sensitivities to climate change, and therefore adaptation to a warming planet represents a challenging new issue for urban policy makers in both the developed and developing world. Further to climate mitigation strategies implemented in various cities over the past 20 years, more recent efforts of urban management have also included actions taken to adapt to increasing temperatures, sea level and extreme events. Through the examination and comparison of seven cities, this paper identifies the various levels of administrative adaptation planning, the tools and information used in making policy choices, and the roles of governance and finance in urban adaptation to climate change. Lessons learned from these seven cases are presented to better inform the next generation of cities adapting to climate change.
Keywords: Q54; Q58; 330; Cities; Urban Areas; Adaptation; Climate Change; Governance